Serving Children with Special Educational Needs: Perspectives from a mainstream and a special school - Anastasiou, Kalia (2009)
The education of children with special educational needs and/or disabilities has for a long time been a major concern for governments globally. ‘Education for All’ is a common phrase amongst policies and legislations as the vision of inclusion in the mainstream is the primarily focus. Specifically the United Kingdom has placed a lot of effort during the last thirty five years or so to minimise the number of special schools and to ensure that the needs of children with SEN are sufficiently met in mainstream settings since they have a right to be educated alongside other children whom in their majority do not have SEN. However, in conjunction with the UK’s ‘inclusion agenda’ another agenda appears to co-exist. The ‘standards agenda’ which has been criticised largely for over-ruling and in many cases minimizing any attempts of inclusivity taking place in mainstream settings. This research is based on a case study of a mainstream and special school seeking teaching staff’s views upon the ‘Education for All’ aim, its current effectiveness and possible negative or positive effects of placing all children with SEN in mainstream education. Overall there seems to be an agreement on the fact that mainstream schools need more support if inclusion is going to be addressed seriously, special schools are still needed and the dilemma of which is the best place for children with SEN to be educated